2015
DOI: 10.1002/pen.24192
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of β phase formation in piezoelectric response of electrospun polyvinylidene fluoride nanofibers: LiCl additive and increasing fibers tension

Abstract: As a piezoelectric polymer, poly (vinylidene fluoride) (PVDF) is attractive in energy conversion applications between electrical and mechanical forms because of its low cost, high flexibility, and biocompatibility. The piezoelectricity of electrospun PVDF polymer is due to changes in the crystalline structure (e.g., creating the β‐phase) during the electrospinning process. This research focuses on two approaches for investigation of β Phase formation: (1) addition of LiCl in different concentrations (0.001, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 39 publications
0
55
0
1
Order By: Relevance
“…Additives can aid the electrospinning process, and also improve the piezoelectric performance of the composites bers. The presence of inorganic salt LiCl of 0.00133 wt% in PVDF DMF/acetone (4/6) solution in 16 wt% concentration, 211 decreased the ber diameter from 340 nm to 65 nm due to the increased charge carried by the jet, and increased the b-phase formation to 93.6%. The voltage response of PVDF was increased from 1.89 V to 8 V for composite bers with 0.00133 wt% of LiCl, which is of interest for harvesting.…”
Section: Structure Of Polyvinylidene Uoride (Pvdf) and Polymorphsmentioning
confidence: 99%
“…Additives can aid the electrospinning process, and also improve the piezoelectric performance of the composites bers. The presence of inorganic salt LiCl of 0.00133 wt% in PVDF DMF/acetone (4/6) solution in 16 wt% concentration, 211 decreased the ber diameter from 340 nm to 65 nm due to the increased charge carried by the jet, and increased the b-phase formation to 93.6%. The voltage response of PVDF was increased from 1.89 V to 8 V for composite bers with 0.00133 wt% of LiCl, which is of interest for harvesting.…”
Section: Structure Of Polyvinylidene Uoride (Pvdf) and Polymorphsmentioning
confidence: 99%
“…[213][214][215][216][217][218][219] It has indeed been demonstrated that aligned PVDF nanofiber arrays possess superior piezoelectric properties compared to random nanofibers meshes. [220][221][222][223] Hence, a very promising research topic is how the molecular configuration of piezoelectric polymers and their polymorphic states relate to the nanofiber geometry and how piezoelectric properties can be induced by electrospinning.…”
Section: Polymeric Fibersmentioning
confidence: 99%
“…It should be noted that the fiber diameter is a factor that has an influence on the piezo‐response of fabricated samples as it was investigated before. Within the context of the efficacy of nanofiber's diameter on the piezoelectric response of PVDF nanofibers, Mokhtari et al [ 26 ] applied two approaches to achieve more content of the β crystalline phase and higher output voltage. In both of those methods, the addition of different concentrations of LiCl salt and applying tension on fiber by high‐speed drum collector, the smaller nanofibers were obtained that enhanced the piezo‐response.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the potential of the prepared nanofibers for sensor and energy harvesting applications, the direct piezoelectric properties were characterized under the pressure mode using dropping ball test as described by Mokhtari et al [ 26 ] First, the samples were placed on a rectangular metal plane. To apply a uniform force on the external surface of the sensor, and also exploit all the exterior parts of the sensor for the voltage creation and avoid from any damage due to successive impacts, a squared plate with the dimension of 2 × 2 cm 2 was used on the samples.…”
Section: Methodsmentioning
confidence: 99%